Differentiated Learning Innovation in Elementary Schools: A Nvivo Analysis of Combined Strategies - Alfurqan Alfurqan; Wirdati Wirdati; Rahmi Wiza; Zilham Usral; Ardi Satrial (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
Learning practices in elementary schools have not fully enhanced students' creativity. The diverse learning needs of students pose challenges in fostering creative and critical learners. Differentiated learning strategies aim to address these needs by adjusting content, processes, and products to match students' abilities and interests. This research explores differentiated learning as an innovation in elementary schools. A qualitative multiple case study design was employed to compare variations and similarities in differentiated learning practices across five selected schools. The schools were chosen based on criteria such as student population, teacher qualifications, and certification percentages. Thirty-two certified teachers with relevant qualifications participated as respondents. Data were analyzed using Nvivo 12 software through coding, categorization, matrix coding, and project mapping. The findings reveal that combined differentiated learning strategies effectively meet students' needs, talents, and interests. These strategies involve integrating varied learning resources and digital media within interactive learning communities. This study provides practical strategies for elementary teachers to enhance student creativity through diverse media and suitable learning environments. The findings support previous research on differentiated learning's role in developing creative, critical, and enthusiastic learners.